The effects of ageing method and time on meat quality attributes of Springbok (Antidorcas marsupialis) Longissimus thoracis et lumborum (LTL) muscle - Wabule, Daphne Enid (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFoodSc)--Stellenbosch University, 2020.